Case report of autosomal recessive spastic ataxia of Charlevoix-Saguenay - Suresh Pandi; Anirudda Deshpande; Supriya Khardenavis (Wolters Kluwer Medknow Publications, 2014)
Autosomal recessive spastic ataxia of Charlevoix-Saguenay is a neurodegenerative disorder characterized by early-onset cerebellar ataxia with spasticity, a pyramidal syndrome and peripheral neuropathy Here, we present a 28-year-old male patient with symptoms of gait instability, distal sensory loss and spasticity since 10 years of age with slow progression and is currently moderately disabled in his daily activities. His nerve conduction studies and neuroimaging were consistent with the diagnosis. Our emphasis would be on the specific magnetic resonance imaging features of the entity, which would help narrow down the genetic testing and provide the practitioner with a rather accurate diagnosis needed for prognostication and valuable counseling thereafter.